Influence of concentration on the radiolytic decomposition of thiamine, riboflavin, and pyridoxine in aqueous solution (2014)
Vitamin loss during irradiation has been claimed as a critical area in food irradiation technology, especially that of thiamine (B1), which has been considered as the most sensitive to radiation. Although it has been suggested that no vitamin deficiency could result from consuming irradiated food, a long debate on the loss of vitamins and other nutrients during food irradiation has been maintained by the lack of experimental studies monitoring decomposition rates at different concentrations and doses. Since thiamine, riboflavin, and pyridoxine are labile vitamins, this study has focused on their radiolytic decomposition in dilute aqueous solutions in the presence of air. The decomposition process was followed by HPLC and UV-spectroscopy. The results obtained in aqueous solutions showed a dependence of the decomposition as a nonlinear function of the dose. Of these three compounds, the decomposition was higher for thiamine than for riboflavin and even less in pyridoxine.